Impact of Pandan Leaf Extract Addition on the Oxidative Degradation of Sunflower Oil during Microwave Heating - M. Abbas Ali; Rafiqqah Mohamad Sabri; Khu, Say Li; Nik Azmi Nik Mahmood (Universiti Kebangsaan Malaysia, 2015)
The efficacy of pandan leaf extract (PLE) addition on the oxidative degradation of sunflower oil (SFO) during microwave heating was studied. 80% of methanol extract showed better antioxidant action than the 100% methanol or ethanol extract and the total phenolic contents, DPPH radical scavenging activity and linoleic acid system of PLE were found to be 1845.50 mg GAE/100 g, 60.62-89.87% and 82.21%, respectively. 80% of methanolic extracts at different concentrations (0.1, 0.2 and 0.4 wt. %) were added to SFO. The antioxidant treated and control oil samples were subjected to microwave heating and were analyzed at regular intervals for the extent of oxidative changes following the measurements of peroxide value, p-anisidine value, TOTOX, free fatty acid, specific extinction, iodine value, viscosity, polar compounds and fatty acid composition. The PLE were found to be quite effective towards suppressing the primary and secondary oxidation products in the tested oil. The order of effectiveness (p<0.05) was BHA > 0.4% PLE > 0.2% PLE > 0.1% PLE > control. The present results suggested that antioxidant extract from pandan leaf might be used to protect vegetable oils from oxidation.